2020
DOI: 10.1111/1756-185x.13909
|View full text |Cite
|
Sign up to set email alerts
|

Understanding immunopathological fallout of human coronavirus infections including COVID‐19: Will they cross the path of rheumatologists?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causing coronavirus disease 2019 (COVID-19) is the biggest pandemic of our lifetime to date. No effective treatment is yet in sight for this catastrophic illness. Several antiviral agents and vaccines are in clinical trials, and drug repurposings as immediate and alternative choices are also under consideration. Immunomodulatory agents like hydroxychloroquine (HCQ) as well as biological disease-modifying anti-rheumatic drugs (bDMARDs) such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 92 publications
1
9
0
10
Order By: Relevance
“…A previous study also showed that this novel coronavirus could also induce secondary anti-phospholipid syndrome (APS) by promoting the production of anti-phospholipid antibodies (APL-Abs) (9). Xiao et al (10) also support this study, which found that 47% of patients with COVID-19 in the intensive unit were positive for APL-Abs. However, it is still unclear whether these antibodies are associated with thrombosis in these patients.…”
Section: Introductionsupporting
confidence: 59%
“…A previous study also showed that this novel coronavirus could also induce secondary anti-phospholipid syndrome (APS) by promoting the production of anti-phospholipid antibodies (APL-Abs) (9). Xiao et al (10) also support this study, which found that 47% of patients with COVID-19 in the intensive unit were positive for APL-Abs. However, it is still unclear whether these antibodies are associated with thrombosis in these patients.…”
Section: Introductionsupporting
confidence: 59%
“…The average incubation period is 5 days ( 3 ), and the most prevalent signs and symptoms are fever, cough, headache, myalgia, fatigue, gastrointestinal symptoms, and dyspnea ( 4 , 5 ). COVID-19 causes distinct clinical manifestations among affected individuals, ranging from asymptomatic cases to cases with mild, moderate, severe, or critical symptoms, where they might progress to an acute respiratory distress syndrome (SARS) or even to dysfunction of multiple organs, complications that lead to death ( 6 , 7 ). The risk of developing a more aggressive disease condition is influenced by age and the presence of comorbidities, such as diabetes, hypertension, obesity, and cardiovascular diseases ( 2 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 We theorize that these statistics are related to women having increased rates of autoimmunity and drug reactions in general. 5 There is reported overlap in the immune response that occurs during COVID-19 infection, after the RNA-based COVID-19 vaccines, and in the autoimmunity of systemic lupus erythematosus (SLE), including its cutaneous manifestations. 5,6 All produce an immune response with increased production of type I interferon (IFN) by plasmacytoid dendritic cells.…”
Section: Discussionmentioning
confidence: 99%